Kewenangan Pejabat Pembuat Akta Tanah Dalam Perjanjian Jual Beli Tanah - Herlina Ratna SN (Universitas Bandar Lampung (UBL), 2015)
Land Titles Registrar is a public official who has the authority to make certain authentic act. The legal basis rests arranged in the BAL, PP 24 In 1997, PP 37 of 1998. This is reflected clearly from the legal institution that is responsible for hiring and firing, duties and authorities in order to make a certain authentic deed, as well as guidance and supervision system Land Titles Registrar. The problem in this paper is how to the role and authority of Land Titles Registrar in land purchase and sale agreement. The research method in this paper is normative and the empirical method, where data is sourced from literature studies and field studies, and analysis of qualitative data. Prove research results that the authorities in the deed is Land Titles Registrar. However, if there are duplicates in a single region and Land Titles Registrar, Land Titles Registrar officials while automatically authorized in the deed is Land Titles Registrar, in this case Land Titles Registrar while not authorized in the manufacture of land deed. People are expected to do a purchase agreement on the ground in front of the competent authority, in this case the Land Deed Official, given the deed made by Land Titles Registrar an authentic act which can be used as evidence in case of dispute.